Vulnerabilities and intersecting issues as contributors to higher risk of transmission and acquisition of HIV - Julius, Mekolle, Enongene (My University, 2022)
The majority of HIV/AIDS programs and research remain focused on preventive and therapeutic approaches, with a key interest in behavioral change. This myopic view ignores the wider framework of the epidemic and disregards some of the more intricate aspects, compared to the direct causes of the disease. This paper attempts to discuss the prevailing factors and how they support the high risk of transmission and acquisition of HIV in society.
Keywords: HIV; Transmission; vulnerability